Organic trace elements enhance growth performance, antioxidant capacity, and gut microbiota in finishing pigs - Xu, Weiwei; Zhou, Miao; Yang, Zhikang; Zheng, Mengli; Chen, Qinghua (Frontiers in Veterinary Science, 2024)
Excessive inorganic trace elements are added to livestock and poultry feed to meet the needs of animals, accompanied by frequent occurrence of excretion and gastrointestinal stress. Replacing inorganic trace elements with organic trace elements provides a promising solution to alleviate these problems. Therefore, this study aimed to assess the impact of replacing all inorganic trace elements (ITMs) in feed on the growth performance, meat quality, serum parameters, trace element metabolism, and gut microbiota of finishing pigs. A total of 128 Duroc × Landrace × Yorkshire growing-finishing pigs (33.88 ± 0.62 kg) were assigned to four treatments in a randomized complete block design. Each treatment was divided into four replicates, each containing eight pigs. The control group received a basal diet containing 100% inorganic trace elements, while the experimental groups were provided with diets where all inorganic trace elements were substituted with 30, 50, and 70% organic trace elements. The experiment spanned 56 days. Results indicated that replacing all ITMs with 30, 50, and 70% OTMs demonstrated no adverse effects on average daily feed intake, average daily gain, feed conversion ratio, eye muscle area, backfat thickness, and relative organ weight of finishing pigs compared to the control group. Furthermore, the replacement led to increased serum immunoglobulin A concentration and Cu-SOD enzyme activity, and decreased serum MDA level, and GSH-Px activity in the liver. Notably, 50 and 70% OTMs increased serum Mn-SOD activity, and 70% OTMs increased serum T-AOC content. Moreover, it significantly decreased the excretion of trace elements in feces without compromising their deposition in the muscle. Additionally, replacing 100% ITMs with 30% OTMs resulted in an improved Shannon index of colonic microbiota in finishing pigs. In conclusion, replacing 100% inorganic trace elements with 30, 50, and 70% organic trace elements exhibited no detrimental effects on the performance of finishing pigs. In conclusion, replacing 100% inorganic trace elements with 70% organic trace elements had certain potential to improve the production performance of finishing pigs. This replacement strategy can enhance meat quality, boost antioxidant capacity, reduce trace element excretion, facilitate trace element absorption and deposition, and enhance gut microbiota homeostasis.